Practice of psycho-cardiology nursing for a patient with hypertension of deficiency of kidney Yang type (1例肾阳虚型高血压患者的“双心护理”体会) - CUI Shujie (崔淑节); HU Yaoyao (胡瑶瑶); ZHANG Linqun (章玲群); XU Meng (徐蒙); REN Pengna (任鹏娜) (中西医结合护理)
This paper summarized the practice of psycho-cardiology nursing for 1 patient with hypertension of deficiency of kidney Yang type. Key issues of nursing included illness condition observation, blood pressure monitoring, medication nursing, Traditional Chinese Medicine characteristic nursing, psychological evaluation and psycho-cardiology education. Under the guidance of Psycho-Cardiology nursing concept, the integrated nursing of traditional Chinese and western medicine were carried out to relieve the clinical symptoms and mental stress, and improve the patient’s adherence to the treatment. (本文总结了1例肾阳虚型高血压患者的“双心护理”体会。护理要点包括病情观察、血压监测、用药护理、中医特色护理等, 并在此基础上给予心理评估、“双心”教育等干预措施。基于“双心护理”模式开展中西医结合护理, 有助于改善患者症状, 缓解心理压力, 提高治疗依从性, 促进患者康复。)